2020
DOI: 10.1001/jama.2020.8711
|View full text |Cite
|
Sign up to set email alerts
|

Planning for a COVID-19 Vaccination Program

Abstract: The long-term solution to the coronavirus disease 2019 (COVID-19) pandemic, hopefully, will be a globally implemented, safe vaccination program that has broad clinical and socioeconomic benefits. Dozens of vaccines are in development, with 8 currently in phase 1 trials. Some scenarios predict the earliest, widespread availability of a COVID-19 vaccine to be in 2021. 1 As launches of prior mass vaccination programs have demonstrated, careful planning to ensure readiness of both the general public and the health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
394
1
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 557 publications
(432 citation statements)
references
References 7 publications
3
394
1
11
Order By: Relevance
“…During the rst 6 months, more than 10 million COVID-19 cases were con rmed worldwide, out of which more than 20 thousand were in Saudi Arabia [3]. Although none of the underdevelopment COVID-19 vaccines have reached the market [4,5], vaccination is considered the most effective strategy for preventing the pandemic and avoiding complications associated with the disease. However, many studies [6,7] have shown that the decision to take available vaccines is dependent on beliefs and perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…During the rst 6 months, more than 10 million COVID-19 cases were con rmed worldwide, out of which more than 20 thousand were in Saudi Arabia [3]. Although none of the underdevelopment COVID-19 vaccines have reached the market [4,5], vaccination is considered the most effective strategy for preventing the pandemic and avoiding complications associated with the disease. However, many studies [6,7] have shown that the decision to take available vaccines is dependent on beliefs and perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…6 The long term solution to COVID-19, however, would most likely be a safe, globally implemented vaccination program with a broad range of clinical and socioeconomic benefits. 7 It is of point to note that vaccination is one of the greatest achievements of modern medicine. It is the greatest human intervention besides clean water and sanitation.…”
Section: Introductionmentioning
confidence: 99%
“…Theorem 2. Suppose that delay between detection and intervention is larger if the case is detected in the other subgroup, σ ≥ and that everything else, the total number of infections and detected cases is the same as in the homogenous case, Z 1 (t) + Z 2 (t) = Z(t) for all t. The stopping time in the homogenous case is then the same as in one of the subgroups but before the stopping time in the other subgroup, τ = τ (2) ≤ τ (1) ≤ τ + σ − .…”
Section: Outbreaks Are Longer With Two Subgroupsmentioning
confidence: 99%
“…Hence, τ = τ + = min τ 1 , τ 2 + = τ (2) . Obviously, τ (2) ≤ τ (1) . The last inequality, τ (1) ≤ τ + σ − follows from the definition of the stopping time (20) and (21).…”
Section: Outbreaks Are Longer With Two Subgroupsmentioning
confidence: 99%
See 1 more Smart Citation